﻿A review of the assassin-fly genus Anypodetus Hermann, 1907 with the description of a new species (Insecta, Diptera, Asilidae) - Torsten Dikow; Meliah Dubus (African Invertebrates, 2023)
The genus Anypodetus Hermann, 1907 (Diptera, Asilidae, Laphriinae) is reviewed. Currently, eight species are recognized from Botswana, Mozambique, Namibia, South Africa, Zimbabwe, and southern-most Zambia, i.e., Anypodetus arachnoides Oldroyd, 1974 widespread, Anypodetus fasciatus Hermann, 1907 widespread, Anypodetus fascipennis Engel, 1924 widespread, Anypodetus leucothrix Londt, 2000 restricted to southern Namibia and south-western South Africa, Anypodetus macroceros Londt, 2000 restricted to west-central Namibia, Anypodetus nigrifacies Ricardo, 1925 restricted to eastern-most South Africa and southern Mozambique, Anypodetus phalaros Londt, 2000 Namibia and South Africa, and Anypodetus unicolor Oldroyd, 1974 Namibia, eastern South Africa, adjacent Mozambique, and southern Zimbabwe. One new species, Anypodetus londti sp. nov. from Mozambique and Zimbabwe, is described for a total of nine species in the genus. Study of the secondary type specimens of A. unicolor from Namibia revealed that these specimens do not represent this species, reducing the number of species recorded from Namibia to six. Anypodetus leucothrix is recorded with several additional collecting events in central and northern Namibia extending its range significantly. Distribution, biology, occurrence in biodiversity hotspots sensu Conservation International, and seasonal imago flight activity are discussed. Diagnoses, photographs, specimen occurrence data, and an identification key to species are provided with the new species described in detail. The sexual dimorphism in the development of the mystax and wing vein variation in regard to the alignment of M2 and M3 are discussed and illustrated.